I-Motif DNA: structural features and significance to cell biology. Issue 16 (16th August 2018) - Abou Assi, Hala; Garavís, Miguel; González, Carlos; Damha, Masad J
Abstract: The i-motif represents a paradigmatic example of the wide structural versatility of nucleic acids. In remarkable contrast to duplex DNA, i-motifs are four-stranded DNA structures held together by hemi- protonated and intercalated cytosine base pairs (C:C + ). First observed 25 years ago, and considered by many as a mere structural oddity, interest in and discussion on the biological role of i-motifs have grown dramatically in recent years. In this review we focus on structural aspects of i-motif formation, the factors leading to its stabilization and recent studies describing the possible role of i-motifs in fundamental biological processes.